2022
DOI: 10.1177/10760296221076152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yangxin Recipe in Combination with Conventional Western Medicine in Treatment of Angina Pectoris of Coronary Heart Disease

Abstract: Objective To study the efficacy of Yangxin Recipe (YXR) in patients with stable angina pectoris of coronary heart disease and its impacts on coronary CT angiography. Methods A total of 78 patients with coronary heart disease and angina pectoris were randomly divided into a control group (n = 39) and a YXR group (n = 39). The control group adopted conventional Western medicine while the YXR group received conventional western medicine + oral administration of YXR. After six months of continuous treatment, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The studies were published between 2006 and 2019. Overall, 42 trials [12,20–60] with 4290 angina-pectoris patients were involved in the network meta-analysis, 2273 in the treatment group and 2017 in the control group. The sample sizes of the study participants ranged from 46 to 432.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were published between 2006 and 2019. Overall, 42 trials [12,20–60] with 4290 angina-pectoris patients were involved in the network meta-analysis, 2273 in the treatment group and 2017 in the control group. The sample sizes of the study participants ranged from 46 to 432.…”
Section: Resultsmentioning
confidence: 99%
“…As is shown in Figure 3, 2 closed loops were formed, focusing on the conventional treatment. 42 RCTs [12,20–60] for angina-pectoris treatment efficiency were estimated according to the efficacy evaluation criteria. ECG effects and hemorheological indicators were included in 40 RCTs [12,20–24,26–55,57–60] and 19 RCTs, [20,21,25–30,33–35,37,38,41,48,49,52,59,60] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…LVEDD refers to the filling volume at the end of the left ventricular diastole, and its normal value is 75 ~ 160 mL. LVESV can reflect the systolic function of the left ventricle and its normal value is < 49 mL/m 2 [25,26]. It was found that LVEDD, LVESV and LVEF in the experimental group were significantly lower than those in the control group, which indicated that high-dose nitroglycerin combined with atenolol could more effectively improve the cardiac function of patients with angina pectoris compared with lowdose nitroglycerin.…”
Section: Comparison Of Incidence Of Adverse Reactions Between the Two...mentioning
confidence: 99%
“…[9–11] It consists of 2 types: stable and unstable angina. [12,13] According to theory of traditional Chinese medicine (TCM), AP belongs to the “ Xiong Bi ,” “chest arthralgia,” and “heartache.” Its major pathogenesis is explained by “heart pulse stasis” and “Qi statsis.” [14–20] Clinical practice has proven that Yangxin Decoction (YXD) has unique advantages for the management of patients with AP of CHD. [21–29]…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Clinical practice has proven that Yangxin Decoction (YXD) has unique advantages for the management of patients with AP of CHD. [21][22][23][24][25][26][27][28][29] Previous studies have reported that YXD can improve the AP of CHD by increasing the levels of serum 6-Keto-PGF 1α, high-density lipoprotein cholesterol, and apolipoprotein A. [30,31] It can also enhance myocardial function and aortic abnormalities.…”
Section: Introductionmentioning
confidence: 99%